Motivation, Belonging, and Support: Examining Persistence in Counseling Programs - Alisa Housenecht; Jacqueline Swank (Teaching and Supervision in Counseling, 2022)
The rising racially and ethnically minoritized population in the U.S. challenges counselor educators to train racially and ethnically diverse counselors; therefore, there is a need to better understand the factors that affect persistence and retention of diverse students in counseling programs. The researchers examined the role of motivation (Academic Motivation Scale), sense of belonging (Campus Connectedness Scale), and social support (Student Academic Support Scale) on the persistence (3-item persistence measure) of 396 master’s level counseling students, including investigating differences between White and minoritized students. Pearson’s correlations results revealed intention to persist was positively correlated with motivation (r(394) = .44, p < .01), belonging (r(394) = .39, p < .01), and social support (r(394) = .01, p < .05) and ANOVA results showed no significant differences were found between White and minoritized students. Counselor educators can improve student experiences by implementing strategies to create a diverse and inclusive community.
Keywords: counselor education; motivation; belonging; support